2012
DOI: 10.5846/stxb201104280561
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of root biomass ofPinus massonianaplantation in Three Gorges Reservoir area, China

Abstract: 摘要:以三峡库区主要植被马尾松人工林为研究对象,用内径为 10 cm 的根钻,分别在马尾松中龄林、近熟林和成熟林内,据树 干 0. 5、1. 0、1. 5 m 和 2. 0 m 处设置取样点,各样点按 0-10、10-20、20-30、30-40、40-60 cm 将土壤分为 5 个垂直层次,对马 尾松根系的空间分布格局进行调查。 结果表明:(1) 三峡库区马尾松总根系生物量(0-10 mm) 为中龄林(4. 72 t / hm 2) 显著高 于成熟林(2. 94 t / hm 2) 和近熟林(2. 40 t / hm 2) (P<0. 05) 。 细根(0-2 mm) 生物量随年龄增加而递减,差异不显著(P>0. 05) ;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This can be explained by the fact that P. massoniana fine roots (diameter ≤ 2 mm) and their mediated plant P uptake mainly occur in top-soil (< 20 cm) rather than deep-soil (Brandtberg et al 2010;Zhu et al 2021). For example, Cheng et al (2012) reported that P. massoniana roots with diameters ≤ 2 mm and < 1 mm were mainly distributed in the 0 − 20 cm and 0 − 10 cm soil layers, respectively. In addition, the study reported by Yang et al (2021) also highlighted that plant root P uptake during forest stand development resulted in a decrease of soil P concentration in 0 − 20 cm layer but not in 20 − 30 cm layer, which also supported our inference.…”
Section: Top-soil Labile P Storage Decreased More Than That At Deep-s...mentioning
confidence: 99%
“…This can be explained by the fact that P. massoniana fine roots (diameter ≤ 2 mm) and their mediated plant P uptake mainly occur in top-soil (< 20 cm) rather than deep-soil (Brandtberg et al 2010;Zhu et al 2021). For example, Cheng et al (2012) reported that P. massoniana roots with diameters ≤ 2 mm and < 1 mm were mainly distributed in the 0 − 20 cm and 0 − 10 cm soil layers, respectively. In addition, the study reported by Yang et al (2021) also highlighted that plant root P uptake during forest stand development resulted in a decrease of soil P concentration in 0 − 20 cm layer but not in 20 − 30 cm layer, which also supported our inference.…”
Section: Top-soil Labile P Storage Decreased More Than That At Deep-s...mentioning
confidence: 99%
“…P. massoniana is an important species in southern China and is also the most widely distributed forest type in the Three Gorges Reservoir area [35]. Few studies have investigated the dynamics of the fine roots of P. massoniana under natural or human management conditions in the Three Gorges Reservoir area [19,36]. We hypothesized that thinning will affect the fine root biomass.…”
Section: Introductionmentioning
confidence: 99%